Faunal Remains from Phum Snay, Banteay Meanchey, Cambodia - von den Driesch, Angela; O’Reilly, Dougald J. W.; Voeun, Vuthy (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
This paper analyses faunal remains excavated from the late prehistoric cemetery of Phum Snay in northwest Cambodia. The material comprises two different components: (1) animal bones as grave goods and (2) bone fragments originating from settlement activities. The mammal and bird remains from the graves derive exclusively from domestic animals and include water buffalo, cattle, pig and possibly a chicken. In most cases, one or two limbs from the left side of the body of one or two species were deposited in a grave. Fish were also incorporated in the grave cult. The animal bones found in the non-burial context reveal a broad spectrum foraging economy that exploited a wide range of ecosystems: forests, grass- and marshlands, rivers and inundated fields, resulting in the capture of deer, boar, smaller carnivores, cranes, tortoises, turtles, monitor lizards, crocodiles, and fish. The article will be available as a PDF in the near future.